SELECTED BIONUTRIENT CONTENTS IN SPAGHETTI SQUASH DEPENDING ON SOWING DATE AND PLANT SPACING - Wanda Wadas; Izolda Borysiak-Marciniak1 (Acta Scientiarum Polonorum: Hortorum Cultus, 2016)
Minerals are the most important compounds for human nutrition that are supplied by vegetables. The content of mineral in vegetables depends on the species and the cultivar, but it is subject to changes under the influence of environmental conditions and agricultural factors. This study examined the effect of sowing date (5, 15 and 25 May) and plant spacing (1 ´ 0.6 m, 1 ´ 0.8 m and 1 ´ 1 m) on selected bionutrient contents (P, K, Ca, Mg and Fe) in the fruits of two spaghetti squash cultivars, ‘Makaronowa Warszawska’ and ‘Pyza’, originating from Poland. A field experiment was carried out in central-eastern Poland on loamy sand soil. Fully-mature spaghetti squash fruits were harvested from the beginning of September to the beginning of October. The sowing date of the spaghetti squash did not affect the dry matter content, K, Ca or Mg in fruits. The P content was the highest for plants sown on 25 May. In contrast, the highest Fe content was found for plants sown on 5 May. The dry matter content was highest in the fruits of plants sown with 1 × 1 m. The increase in the distance between plants in a row from 0.6 to 0.8 or 1 m resulted in a decrease in Fe content only for plants sown on 15 May. Plant spacing did not have a significant effect on the remaining bionutrient content in the spaghetti squash fruits. The content of dry matter, P, K, Ca, Mg and Fe in the fruits of both cultivars did not differ significantly, although ‘Pyza’ tended to accumulate the most Ca and had lower K and Fe levels.